Teaching strategies in language classes - M. del M. Palenzuela Pérez; O. Murashkina (Ибероамериканские тетради, 2015)
Because of the diversity in the classroom, the teacher should develop a series of strategies that allow you to transmit knowledge effectively. Teaching is difficult, even more, in second language classroom, where in addition to the student´s individual differences, such as cognitive styles, motivation and self-esteem, are added others, such as nationality, age or mother tongue.This paper describes the role of the teacher in the classroom and the teaching strategies implemented in the classroom in a context of formal education. Strategies have been developed from the precepts postulated by the theory of multiple intelligences.